Syphilis and hiv infection: historical and cientifics correlations - Brandão, José Eduardo; Sá, Carlos Alberto M. de; Asensi, M.D. (Brazilian Journal of Sexually Transmitted Diseases, 2002)
The syphilis can be defined as disease of permanent present lime. The conquests in the diagnosis fields and therapy come being insufficient for the control of the disease. and the epidemic problem stays current and serious. Fhe T pallidum can persist for long time in the host. The syphilis is common in patient HIV. however. not very it is known about the form as lhe apprenticeship of the infection for Hl V it could affect the clinical-laboratories manifestations of the disease. In patients with HIV, the syphilis can have an accelerated course and the serologics results of infection can be blocked or altercd. Besides. several raports in the literature have been documenting significam alterations in the natural history of the disease in individuais with positive serologics for HIV, still hindering more the diagnosis laboratories for the methods classic serologics. It is necessary, therefore, besides a standardization of tests diagnoses, the implementation of techniques thal facilitate lhe detection of the bactéria, and a new control program to both infections.